“Hybrid Governance” and the Politics of Legitimacy in the Myanmar Peace Process - Ashley South (2018)
© 2017 Journal of Contemporary Asia This article examines competing claims to political legitimacy and sovereignty in Myanmar’s conflict-affected areas of “limited statehood.” In the context of ceasefires and an emerging peace process since 2012, non-state-controlled “liberated zones” and areas of mixed insurgent and government authority constitute new political spaces, where multiple state and para-state actors demonstrate governance authority, extract resources and provide services to local communities. This article explores the dynamics and implications of these developments with reference to the emerging literatures on “rebel rulers” and “hybrid governance,” and examines the practices of donors and aid agencies operating in these areas. I argue that external actors seeking to “think and work politically” should move beyond standard peace-building and development packages based on strengthening the state, and adopt more conflict and context-sensitive approaches. Effective state building should take account of governance structures and service delivery functions established by ethnic armed organisations, which although under-resourced enjoy significant political legitimacy.